Cryo-EM structure and evolutionary history of the conjugation surface exclusion protein TraT - Chloe Seddon; Sophia David; Joshua L. C. Wong; Naito Ishimoto; Shan He; Jonathan Bradshaw; Wen Wen Low; Gad Frankel; Konstantinos Beis (Nature Communications)
Abstract Conjugation plays a major role in dissemination of antimicrobial resistance genes. Following transfer of IncF-like plasmids, recipients become refractory to a second wave of conjugation with the same plasmid via entry (TraS) and surface (TraT) exclusion mechanisms. Here, we show that TraT from the pKpQIL and F plasmids (TraTpKpQIL and TraTF) exhibits plasmid surface exclusion specificity. The cryo-EM structures of TraTpKpQIL and TraTF reveal that they oligomerise into decameric champagne bottle cork-like structures, which are anchored to the outer membrane via a diacylglycerol and palmitic acid modified α-helical barrel domain. Unexpectedly, we identify chromosomal TraT homologues from multiple Gram-negative phyla which form numerous divergent lineages in a phylogenetic tree of TraT sequences. Plasmid-associated TraT sequences are found in multiple distinct lineages, including two separate clades incorporating TraT from Enterobacteriaceae IncF/F-like and Legionellaceae F-like plasmids. These findings suggest that different plasmid backbones have acquired and co-opted TraT on independent occasions.